Lignin-chitosan-based bioplastics from oil palm empty fruit bunches for seed coating; Biocatalysis and Agricultural Biotechnology; Vol. 62 - Ayu A. E. Agustiany Erika; Sarip N. D. Nawawi Deded; Di Martino A. Antonio; Puspita S. F. Sari Fahriya; Fatriasari W. Widya (2024, 2024)
Title screen